Serum levels of the adipokine Pref-1 in gestational diabetes mellitus. Issue 2 (February 2015) - Wurst, Ulrike; Ebert, Thomas; Kralisch, Susan; Stumvoll, Michael; Fasshauer, Mathias
Highlights Pref-1 is not dysregulated in patients with gestational diabetes mellitus (GDM). Pref-1 is not associated with markers of glucose metabolism during pregnancy. Pref-1 is negatively and independently associated with BMI and CRP in pregnancy. Pref-1 is probably not a major contributor to GDM pathophysiology. Pref-1 is positively correlated with gestational age, TG, and creatinine.